Analisa Likuiditas, Solvabilitas, Profitabilitas dan Economic Value Added terhadap Return Saham - Eva Listyarini; Sri Hermuningsih; Gendro Wiyono (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2021)
This study aims to reveal the effect of Liquidity, Solvency, Profitability and Economic Value Added to the Stock Return of Companies with Dividend Policy as a moderating variable. The study uses a quantitative approach, taking the data presented in the company's financial statements. The population is the companies listed on the LQ45 BEI in 2016-2019, and the purposive sampling method produces 28 companies to be observed. The results of smartPLS data analysis show that 1) Liquidity and EVA have a positive and insignificant effect on stock returns 2) Solvency and Dividend Policy have a positive and significant effect on stock returns 3) Profitability has a negative and insignificant effect on stock returns 4) Dividend policy unable to moderate liquidity, solvency, and profitability on stock returns 5) Dividend policy can moderate EVA on stock returns.